2019
DOI: 10.1038/s41467-019-08934-3
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of key whole-brain transitions and dynamics during human wakefulness and non-REM sleep

Abstract: The modern understanding of sleep is based on the classification of sleep into stages defined by their electroencephalography (EEG) signatures, but the underlying brain dynamics remain unclear. Here we aimed to move significantly beyond the current state-of-the-art description of sleep, and in particular to characterise the spatiotemporal complexity of whole-brain networks and state transitions during sleep. In order to obtain the most unbiased estimate of how whole-brain network states evolve through the huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
194
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 209 publications
(203 citation statements)
references
References 67 publications
6
194
0
3
Order By: Relevance
“…This calls for a brain-state-informed analysis of functional connectivity in task-free "resting state" studies, both in humans as well as in animal models. Human subjects may transition between these brain states when they fall asleep 84 . Even more so, animals react differently to the same anaesthetic regimen 83 .…”
Section: Implications On Resting State Studiesmentioning
confidence: 99%
“…This calls for a brain-state-informed analysis of functional connectivity in task-free "resting state" studies, both in humans as well as in animal models. Human subjects may transition between these brain states when they fall asleep 84 . Even more so, animals react differently to the same anaesthetic regimen 83 .…”
Section: Implications On Resting State Studiesmentioning
confidence: 99%
“…2E, Fig. S1) is archetypical of reduced in arousal associated with early sleep-like behaviour in both humans and macaques (Chang C et al 2016;Liu X et al 2018;Stevner ABA et al 2019). Hence, we postulated that by monitoring intrusions of the fMRI activity map associated with EEGtheta activity, we may be able to infer sleep onsets in the fMRI data from the study 2 without the need for simultaneous EEG recordings.…”
Section: A Methods For Detecting Sleep Onsets In the Awake Human Brainmentioning
confidence: 92%
“…This result is compatible with the integrated information theory of consciousness [3][4][5][6][7] , which holds that different levels of consciousness must correspond to the capacity of the brain to integrate information. Many other studies have shown that integration is impaired during non-wakefulness 10,85,86 .…”
Section: /19mentioning
confidence: 93%